Impact of Stopping Tumor Necrosis Factor Inhibitors on Rheumatoid Arthritis Patients' Burden of Disease. Issue 4 (29th March 2018) - Ghiti Moghadam, Marjan; ten Klooster, Peter M.; Vonkeman, Harald E.; Kneepkens, Eva L.; Klaasen, Ruth; Stolk, Jan N.; Tchetverikov, Ilja; Vreugdenhil, Simone A.; van Woerkom, Jan M.; Goekoop‐Ruiterman, Yvonne P. M.; Landewé, Robert B. M.; van Riel, Piet L. C. M.; et al.
Abstract : Objective: To determine the impact of stopping tumor necrosis factor inhibitor (TNFi) treatment on patient‐reported outcomes (PROs) of physical and mental health status, health utility, pain, disability, and fatigue in patients with established rheumatoid arthritis (RA). Methods: In the pragmatic, 12‐month POET trial, 817 RA patients with ≥6 months of remission or stable low disease activity were randomized 2:1 to stopping or continuing TNFi. In case of flare, TNFi was restarted at the discretion of the rheumatologist. PROs were assessed every 3 months. Results: TNFi was restarted within 12 months in 252 of 531 patients (47.5%) in the stop group. At 3 months, mean PRO scores were significantly worse in the stop group, and a larger proportion of patients experienced a minimum clinically important difference (MCID) on all PROs. Effect sizes (ES) were strongest for health utility (ES −0.24) and pain (ES −0.30). Mean scores improved again after this point, but disability scores remained significantly different at 12 months. After 12 months, the relative risk of experiencing an MCID ranged from 1.16 for mental health status to 1.58 for fatigue. Mean PRO scores for patients restarting TNFi within 6 months were no longer significantly different from those that did not restart TNFi at 12 months. Conclusion: Stopping TNFi had a significant negative short‐term impact on a broad range of PROs. Long‐term negative consequences appeared to be limited, and outcomes in patients needing to restart TNFi within the first 6 months tended to be restored at 12 months.